Tantangan dan Strategi Perbankan Dalam Menghadapi Perkembangan Transformasi Digitalisasi di Era 4.0 - Tambunan, Ria Tifanny; Padli Nasution, M. Irwan (MES Bogor, 2023)
The purpose of this research is to study the current Industrial Revolution 4.0 which will affect major changes in digital technology. Digitalization can affect the development of various industries very quickly. One of them is the growing business sector more efficiently and effectively. Therefore, technological advances in the business world can encourage the business world to continue to innovate and launch new products so as not to be eroded by time. Digital transformation is not just a transition from traditional banking to a digital world, it is a major shift in how banks and other financial institutions learn, interact and satisfy their customers. Digital transformation begins with understanding digital customer behavior, likes and dislikes, and the shifts that lead to major organizational shifts from product-centric to customer-centric. Banking needs in this digital era are everywhere at any time. Therefore, banking needs innovation, resilience, security, optimization, and drive to meet the demands of tech-savvy customers. If a bank does not meet customer needs, customers are willing to move to another bank that meets their needs. Keywords: Digitalization, Islamic Banking, Revolution 4.0